Synthesis and Characterization of Mixed Ligand Complexes of Nickel(II) with Histidine and Hippuric Acid - KUMAR, G. (Asian Journal of Chemistry, 2024)
Mixed ligand complexes of nickel(II) with the compositionNa2[Ni{(C6H5CONHCH2COO)(C6H8N3O2)·H2O}]·7H2O and Na2[Ni{(C6H5-CONHCH2COO)(C6H8N3O2).H2O}]·H2O formed with histidine andhippuric acid have been synthesized. The mode of coordination andtheir structures have been examined by elemental analysis, infrared,electronic spectra and magnetic measurements. Histidine has shown atridentate behaviour with the coordination occurring through the carboxylateoxygen atom and two nitrogen atoms of the imidazole and -NH2groups. Hippuric acid has been found to act as a bidentate ligand coordinatingthrough carboxylate oxygen atom and the nitrogen of the amidogroup.